2018
DOI: 10.1111/imcb.12055
|View full text |Cite
|
Sign up to set email alerts
|

The changing face of hematopoiesis: a spectrum of options is available to stem cells

Abstract: For more than 30 years, the scheme whereby bone marrow hematopoietic stem cells give rise to the many different types of blood and immune cells has been represented as a lineage tree diagram. In this model, hematopoietic stem cells follow a preferred route to each of the end-cell types and gradually restrict their other lineage options via a series of intermediate oligo-potent progenitors. Recent findings of lineage biases or affiliations within hematopoietic stem and progenitor cells that are either pluripote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 58 publications
1
11
0
Order By: Relevance
“…Our 'developmental' view of haematopoiesis is that an HSC selects one lineage from a continuum of all end-cell options, and then differentiates to that cell type ( Figure 2). We provided evidence to support our viewpoint elsewhere [45][46][47]. Though the model shows that affiliation/commitment to a cell lineage can occur as early as during the HSC stage, haematopoiesis still remains dynamic.…”
Section: Do Normal Stem Cells Behave Differently?supporting
confidence: 71%
See 2 more Smart Citations
“…Our 'developmental' view of haematopoiesis is that an HSC selects one lineage from a continuum of all end-cell options, and then differentiates to that cell type ( Figure 2). We provided evidence to support our viewpoint elsewhere [45][46][47]. Though the model shows that affiliation/commitment to a cell lineage can occur as early as during the HSC stage, haematopoiesis still remains dynamic.…”
Section: Do Normal Stem Cells Behave Differently?supporting
confidence: 71%
“…Dispersal of HPCs from the bone marrow in a semisolid medium with the addition of particular growth factors (colony-stimulating factors) leads to the production of colonies containing various cell types depending on the added growth factor(s). We argued that the single cell giving rise to the colony 'shuffles sideways' to adopt various pathways because it is out of its normal environment with regard to the control of cell fate [46]. Single-cell analysis of mixed-lineage states has led to the proposal that bursts of alternative gene expression are an important feature of cell decision making, including the existence of bilineage states [51].…”
Section: Do Normal Stem Cells Behave Differently?mentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from influencing the survival, expansion and effector function of mature immune cells in peripheral lymphoid organs, cytokines also have a crucial role in the continuous generation of all blood cell lineages (hematopoiesis), which occurs in the bone marrow and thymus. During hematopoiesis cytokines can influence the lineage output of hematopoietic progenitors by selectively promoting their survival, proliferation or developmental potential ( 1 3 ). Two of the most important cytokines for the generation of lymphoid cells are Flt3-ligand (FL) and Interleukin-7 (IL-7).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in order to demonstrate their instructive role, it is necessary to use a high level of cytokine in in vitro experiments. A graded response of cells to cytokines may be important for steady state versus hematopoiesis under stress conditions, such as infection, whereby the different requirements are survival/expansion versus survival/expansion coupled to a rapid and emergency, diversion of cells towards a required end cell type [ 101 ]. Recent evidence to support this viewpoint is that Singh and colleagues have observed that during chronic erythroid stress, in Epo transgenic mice, HSC exhibit a vastly committed erythroid progenitor profile together with enhanced cell division [ 102 ].…”
Section: Does the Environment That Cells Reside In Instruct Cell Fmentioning
confidence: 99%